Case Series: Cystic Brain Metastases Managed With Reservoir Placement and Stereotactic Radiosurgery. Issue 4 (8th October 2021) - Park, David J; Unadkat, Prashin; Goenka, Anuj; Schulder, Michael
Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) has become one of the mainstays of treatment for patients with metastatic brain tumors. However, metastatic tumors with a large cystic component often exceed the size limit for safe and effective SRS. In such cases, surgical resection may not be the preferred first method of treatment, due to tumor location, patient co-morbidities, and patient preference. In these patients, volume reduction by cyst aspiration (CA) followed by SRS may be a viable alternative treatment option. OBJECTIVE: To present the treatment of patients with cystic metastases using reservoir placement followed by SRS. METHODS: Nine patients were treated with this method. We performed reservoir insertion for the aspiration of cystic component in each patient and followed that with outpatient SRS. RESULTS: Mean overall volume reduction from this treatment method was 78.5%. Mean volume reduction from the CA alone was 59.8%, and after SRS, a further 66.6%, accounting for some cyst reaccumulation between the time of surgery and SRS. Repeat reservoir aspiration was done a total of 10 times in 5 patients. Our study showed local tumor control in 7 of 9 patients (77.8%), while 2 patients required later surgical resection of their tumors. CONCLUSION: CA with reservoir placement followed by SRS is a good option for patients with large cystic brain metastases. The reservoir allows for repeat aspiration if needed. Catheter placement at the center of the cyst, and SRS within 2 to 3 wk of surgery, can maximize the likelihood of a successful outcome.